1994
DOI: 10.1111/j.1365-2796.1994.tb01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima‐media thickness: correlation with the British Regional Heart Study risk score

Abstract: It is concluded that the IMT may be a useful surrogate end-point or biological marker of coronary artery disease and might be considered for use in prospective studies and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 6 publications
2
41
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, a positive relationship between IMT and risk scores was also reported for the British Heart Study, Framingham, and EPOZ risk scores. [41][42][43] However, these studies concerned general populations, ie, subjects who were on average at a relatively low risk for cardiovascular disease, whereas the present study was conducted in a population at high risk. Our findings indicate that the associations of IMT and distensibility with cardiovascular risk also apply to high-risk populations.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Furthermore, a positive relationship between IMT and risk scores was also reported for the British Heart Study, Framingham, and EPOZ risk scores. [41][42][43] However, these studies concerned general populations, ie, subjects who were on average at a relatively low risk for cardiovascular disease, whereas the present study was conducted in a population at high risk. Our findings indicate that the associations of IMT and distensibility with cardiovascular risk also apply to high-risk populations.…”
Section: Discussionmentioning
confidence: 98%
“…1 These useful surrogate markers of cardiovascular disease can now be measured noninvasively by high-resolution B-mode ultrasound. [2][3][4][5][6][7][8][9][10] Reports have shown close associations between these parameters and conventional cardiovascular risk factors, including type 2 diabetes, hypertension, obesity, dyslipidemia, and smoking. [11][12][13][14][15][16][17] Impaired endothelium-mediated regulation of vascular tone has been associated with the presence of coronary atherosclerotic lesions 2,3 and has been observed in patients with traditional cardiovascular risk factors, even in the absence of atherosclerotic lesions.…”
mentioning
confidence: 99%
“…4 Recent studies have reported that endothelial dysfunction is a predictor of cardiovascular events. 5,6 Similarly, increases in the carotid intima-media thickness (IMT) are closely associated with cardiovascular disease 7,8 and predictive of cardiovascular risk. 9 Type 2 diabetes is closely associated with microvascular and macrovascular disease, the major causes of morbidity and mortality in these patients.…”
mentioning
confidence: 99%
“…Thomas et al (2002) reported that many patients with SLE are likely to have asymptomatic atheromatous vascular disease. In the study of 175 women, 40% had focal plaques identified in their carotid arteries by Bmode ultrasound (Manzi et al, 1999), which are often associated with atheroma in other vascular beds, especially the coronary arteries (Frcs et al, 1994;Chambless et al, 1997). The high risk of coronary artery disease complications associated with SLE after adjustment for conventional risk factors had led to the suggestion that SLE itself is an independent cardiovascular risk factor (Urowitz and Gladman, 2000).…”
Section: Discussionmentioning
confidence: 99%